Politeness in Banker-Customer Interactions of Selected Banks in Nigeria’s Yenagoa Metropolis - OYADIJI, Olushola; ODEBIYI, Idowu Paul; ALIYU, Adekemi Edith (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
This study investigates politeness expressions in banker–customer interactions within selected Nigerian banks, contributing to research in interactional pragmatics and politeness studies. It aims to explicate the nature of politeness behaviour in the banking domain, the factors motivating such behaviour, how co-interactants interpret these behaviours, and the extent to which context shapes politeness practices. The data comprise sixty purposively selected interactions between bankers and customers. Using a complementarist adaptation of Lim and Bowers’ Face Theory and Locher and Watts’ Relational Work Theory, the study adopts a descriptive analytical approach. Findings reveal that politeness constitutes a central component of banker–customer interactions, with bankers bearing a greater burden of conflict management and redirecting talk towards the polite end of the relational scale. Customers, in contrast, frequently display impoliteness, while retaliatory responses from bankers remain rare. Although politeness behaviour is cyclical, communication breakdown is uncommon, as the need to achieve interactional goals motivates participants to mitigate potential rifts induced by impoliteness. The study recommends expanded inquiry into the influence of familiarity among bank staff on politeness choices.